(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the presentation of grammatical categories in "Favaid al-Ziyaiya," a significant 15th-century work by Abdurrahman Jami. The study analyzes the interpretation of grammatical concepts, their linguistic analysis, methods of classifying grammatical categories, and their scientific characteristics in the work.